Ergonomic working posture in simulated dental clinical conditions: Effect of magnification on the operator’s experience - Wajngarten, Danielle [UNESP]; Pazos, Júlia Margato [UNESP]; Sasso Garcia, Patricia Petromilli Nordi [UNESP] (PeerJ, 2021)
Objectives. This study observed the effect of different magnification systems on working posture and neck angulation during cavity preparation procedures according to operator’s experience. Methods. This was a laboratory study. The response variables were the neck angulation and the working posture adopted during Class I cavity preparations (N = 640) that were performed under four conditions (unaided visualization, simple loupe, Galilean loupe and Keplerian loupe). Working postures were recorded and evaluated by the Compliance Assessment of Dental Ergonomic Posture Requirements (CADEP). The two-factor ANOVA and Games-Howell post-hoc test were performed (α = 0.05). Results. For all treated teeth it was observed higher posture scores and lowest neck angulations while using the Galilean and Keplerian loupes (p < 0.01). No correlations were found between operator’s experience and working posture (p = 0.71–0.88). Conclusion. It can be concluded that Galilean and Keplerian loupes helped operators to maintain an ergonomic posture and lower neck angulations for all teeth and the operator’s experience provided better ergonomic posture for the mandibular teeth.
Keywords: Dental education; Magnification; Professional practice